(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In connection with the above, the purpose of this study was to study the risk factors leading to the development of massive obstetric hemorrhage. An analysis of 302,000 birth histories in the Samarkand region for the period 2021-2023 was conducted, among which 51 cases of MOH were identified during childbirth and the postpartum period, which amounted to 0.2%. Clinical, laboratory, functional and statistical research methods were used.